STUDENT’S VOICES ON LANGUAGE LEARNER AUTONOMY IN DISTANCE LEARNING - Nurkamilah Nurkamilah; Desy Qomariyatil Badriyah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
Learner autonomy is a complex construct which becomes the focus of language learning, consisting of four dimensions which later are summed up into three, such as initiating, monitoring, and evaluating. The study aimed to know students’ perception and behaviors on learner autonomy in distance learning. The data was gathered from 187 students in the population, but only 43 returned the questionnaire. The 61 items questionnaire was analyzed and found that in the initiating category, most students perceive the learner autonomy positively and indicate the behavior of dreaming to be a good English speaker. While the monitoring category shows the item of modifying methods to find which suits them best. The third category is reflected in their being eager to find out their English proficiency by taking TOEFL tests and the like, voluntarily. While the behavior which is related to ICT or online learning is their willingness to use English to communicate with strangers on the Internet.